HEALTH LOCUS OF CONTROL PASIEN GAGAL GINJAL TERMINAL YANG MENJALANI HEMODIALISIS - Gusti Ayu Ary Antari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Patient with kidney failure who are undergoing hemodialysis routine needs to carry out various disease management including long-term hemodialysis. Beliefs are known to control patient health. Health locus of control becomes a concept regarding the patient’s belief and has control in their health status. This study aimed to identify a health locus of control in a hemodialysis patient. This study used a cross-sectional design. One hundred hemodialysis patients completed the multidimensional health locus of control scale. Data were collected in the Hemodialysis Room at RSD Mangusada and RSUD Wangaya during July-August 2019. The results showed that the mean internal health locus of control was higher than chance and powerful others, namely 29.35; 22.45; and 27.95. The respondents in this study indicate that they believed themselves exerted more control over their health than other people, doctors, and chance. These results serve as important information regarding the health control beliefs of hemodialysis patients.